2019
DOI: 10.1071/mf18031
|View full text |Cite
|
Sign up to set email alerts
|

Assessing alpha and beta diversities of benthic macroinvertebrates and their environmental drivers between watersheds with different levels of habitat transformation in Japan

Abstract: Little is known about differences in species diversity among ecological communities subject to different levels of human-caused habitat transformation and how this disturbance contributes to diversity through symbiotic dependencies with the environment in freshwater ecosystems. We estimated α and β diversities of benthic macroinvertebrates and relationships between diversity and environmental variables in Ado River (natural) and Yasu River (intermediately disturbed) watersheds, Japan. Alpha diversity was cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…More importantly, the evenness of local communities was lower during the irrigation period than during the nonirrigation period, suggesting higher β‐diversity among the former. When comparing spatial patterns of benthic macroinvertebrate communities between the moderately disturbed Yasu River and the less disturbed Ado River within the Lake Biwa watershed, Ko et al (2019) found that the β‐diversity was higher for the former, despite the lower species richness. The Yasu River has a different pattern of land‐use types in its catchment (i.e., 57.7%, 22.5%, and 6.5% for forest, cropland, and urban land use, respectively) compared with that of the Ado River (91.5%, 3.7%, and 0.7%, respectively); thus, there is higher spatial heterogeneity of local stream environments in the former catchment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More importantly, the evenness of local communities was lower during the irrigation period than during the nonirrigation period, suggesting higher β‐diversity among the former. When comparing spatial patterns of benthic macroinvertebrate communities between the moderately disturbed Yasu River and the less disturbed Ado River within the Lake Biwa watershed, Ko et al (2019) found that the β‐diversity was higher for the former, despite the lower species richness. The Yasu River has a different pattern of land‐use types in its catchment (i.e., 57.7%, 22.5%, and 6.5% for forest, cropland, and urban land use, respectively) compared with that of the Ado River (91.5%, 3.7%, and 0.7%, respectively); thus, there is higher spatial heterogeneity of local stream environments in the former catchment.…”
Section: Discussionmentioning
confidence: 99%
“…Stream benthic macroinvertebrates, which are sensitive to environmental changes and serve as a useful indicator of water quality and habitat degradation, not only have important influence on nutrient cycles, primary productivity, decomposition, and translocation of materials, but also constitute an important source of food for fish in freshwater ecosystems (Wallace and Webster 1996, Ogbeibu and Oribhabor 2002). Studies have demonstrated the influence of environmental factors, including physical, biological, and chemical, on the distribution, abundance, and community composition structure of benthic macroinvertebrates and, consequently, leading to a certain change in benthic macroinvertebrate diversity (Rousi et al 2011, Ko et al 2019). For example, low water temperature but high DO formed suitable environments for high diversity and abundance of benthic macroinvertebrates in the Baltic Sea.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation